Three-Dimensional Finite Element Analysis on Mandibular Biomechanics Simulation under Normal and Traumatic Conditions - Mihaela Hedeșiu; Dan George Pavel; Oana Almășan; Sorin Gheorghe Pavel; Horia Hedeșiu; Dan Rafiroiu (MDPI AG, 2022)
The main objective was to examine the biomechanical behavior of the mandible under standardized trauma and to develop models of biomechanical responses when the mandible is subjected to various simulated impacts. A homogenous model based on the bone's average mechanical properties was used. To simulate external loads on the mandible, forces on the chin, forces in an anteroposterior direction, and forces from the basilar edge were applied. To simulate mandibular biomechanics, we employed a model created in the ANSYS v19.0 software. The skull with the temporomandibular joint (TMJ) from the Grabcad website was used as the geometric mandibular model. We attempted to simulate the stresses developed in the mandible by impact forces. The amount of force (F) corresponded to the fall of a five-kilogram body (the head), from a height of two meters (F = 6666.7 N). The impact force was applied perpendicular to an arbitrary surface of an area of 10−3 m2. Impact on the chin region and lateral impact on the mandible, from the basilar edge to the gonion were examined. The investigated clinical situations were mandibular complete dentition; jaw with missing mandibular molars; missing third molar and first and second premolars; missing canine, third molar, first and second premolars, and complete edentation. In a normal bite, the highest stress was on the TMJ area. In case of impact on the chin, in complete edentation, a mandibular fracture occurred; in case of impact on the gonion, all stress values exceed the limit value above which the mandible in the condyle area may fracture.